ORTHOPAEDIC EMERGENCY CASES AT HASAN SADIKIN HOSPITAL BANDUNG CAUSED BY TRADITIONAL BONE SETTER PRACTICE - Hantonius Hantonius; Hermawan Nagar Rasyid; Gibran Tristan Alpharian (Journal Orthopaedi and Traumatology Surabaya, 2018)
Traditional bone setting is common in developing nations. The practitioners are barely educated and rely so much on experience. Although they are popular in public, traditional bone setter are known in hospital practice for their failures and complications which present to hospitals for remediation.The purpose of the study is to report the orthopaedic emergency cases  caused by the practice of traditional bone setter. This was an observational descriptive study, 36 patients with complications after practice of traditional bone setters and subsequently presented to emergency ward in Hasan Sadikin Hospital between 1st January 2015 and 31st August 2017 were evaluated.Among emergecy orthopaedic cases at Hasan Sadikin Hospital caused by bonesetter practice, compartment syndrome and gangrene are the most common complications occured. Twenty patients (56%) with infected wound and compartment syndrome had successful operation., thirteen patients (36%) with gangrene of the extremities had amputations, and three patients (11%) with multiple organ failure died. Twelve percent of amputations in our centre were related to bonesetter practice.The result of this study indicates that traditional bone setters practice may caused patients to develop complications, lose their limbs even lives due to inappropriate treatments.